PANoptosis: a potential target of cardiomyopathy - Sun, Mingli; Lu, Changxu; Wei, Jinwen; Gao, Can; Dong, Dan (Frontiers in Immunology, 2025)
Cardiomyopathy is a group of heterogeneous myocardial diseases that seriously threaten patients. Because the underlying molecular pathogenesis of cardiomyopathy is still unclear, treatment options are still limited to palliative drug therapy. Hence, unraveling the molecular pathways that drive the onset and progression of cardiomyopathy is crucial for identifying effective therapeutic targets and devising clinical intervention strategies. Programmed cell death (PCD) is a type of cell death mediated by specific molecular pathways and genetically regulated, among which pyroptosis, apoptosis, and necroptosis are the main forms. Recently, researchers have uncovered that the intricate interplay among various forms of PCD has given rise to the concept of “PANoptosis,” which represents an integrated cell death process. Recent studies have found that PANoptosis is a key mediator of cardiomyopathy and is expected to become a potential therapeutic target for improving the prognosis of this disease. This review aims to summarize the current progress in understanding the association between PANoptotic activation and cardiomyopathy, and to explore new therapeutic targets and strategies for treating cardiomyopathy.